The Religious Left in Modern America Doorkeepers of a Radical Faith (Palgrave Studies in the History of Social Movements, 2018)
This edited collection of exciting new scholarship provides comprehensive coverage of the broad sweep of twentieth century religious activism on the American left. The volume covers a diversity of perspectives, including Protestant, Catholic, and Jewish history, and important essays on African-American, Latino, and women's spirituality. Taken together, these essays offer a comparative and long-term perspective on religious groups and social movements often studied in isolation, and fully integrate faith-based action into the history of progressive social movements and politics in the modern United States. It becomes clear that throughout the twentieth century, religious faith has served as a powerful motivator and generator for activism, not just as on the right, where observers regularly link religion and politics, but on the left. This volume will appeal to historians of modern American politics, religion, and social movements, religious studies scholars, and contemporary activists.